Formulation and Evaluation of the Physical Properties of Anti-Acne Cream Containing Methanol Extract of Ashitaba Herb (Angelica keiskei) - Hidayati, Agriana Rosmalina; Hidajat, Dedianto; Hajrin, Wahida; Hanifa, Nisa Isneni; Andanalusia, Mahacita; Hidayati, Regina Tria; Rizki, Alpa Alfi; Prianggawe, Prianggawe; Ramadhan, Muhammad Rafi Bintang; Rizkika, Adila (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Ashitaba herb contains flavonoids, phenolics, tannins, alkaloids, and terpenoids, which are known to have antioxidant, antibacterial, and anti-inflammatory properties. Therefore, ashitaba has the potential to be developed into anti-acne preparations, one of which is cream. Creams have various advantages, namely the ability to deliver hydrophilic and hydrophobic compounds better, provide better moisture, and have emollient and occlusive properties by forming a protective layer on the skin and maintaining skin hydration longer. The purpose of this study was to determine the physical properties of methanol extract cream preparations of ashitaba herb. The research method used was laboratory experimental. Ashitaba herb was extracted using the sonication method with 80% methanol solvent to produce a solid extract. The ashitaba herb's methanol extract was combined to create a cream preparation, and its physical characteristics such as homogeneity, pH, viscosity, spreadability, adhesion, and cream type were assessed. The physical property testing revealed that the cream preparation had a unique scent, a thick consistency, and a green hue. This resulted in a homogenous oil-in-water (O/W) type cream preparation with a pH of 6.29, viscosity of 37.050 cp, spreadability of 5.23 cm, and adhesion of 4.59 seconds. Thus, it can be said that the production of the methanol extract of ashitaba herb cream satisfies the requirements and has good physical qualities.